Friday, May 24, 2013

Remember the change of base formula when solving a logarithm that is not base 10.

Log(base 3) 11 = Log 11/Log 3

It's easy to see how this comes about when rewriting the log in exponential form and then solving for y.

y = log(base 3) 11

3^y = 11

Take the log of both sides to get

log(3^y) = log 11

ylog 3 = log 11

y = log11/log3

Instead of having to rewrite as an exponential equation and solving, simply use the change of base formula. In general

Log(base b)a =  Log a/Log b

No comments:

Post a Comment